Optimization of performance and composition for glass ceramics prepared from mixing molten slags - LI Yu; YI Yao-dong; CHEN Kui-yuan; MENG Xin-yang (工程科学学报)
The direct preparation of materials from high-temperature slag is an effective way for the integrated utilization of slags and their thermal energy. In this paper, with ferronickel slags and blast furnace slags as the main raw materials, glass ceramics were prepared by the Petrurgic method, a one-step heat-treatment method by direct crystallization of the slag melt during its cooling process. The ratio of ferronickel slags and blast furnace slags, Mg2+ content, and the effect of nucleating agent TiO2 on the microstructure and properties of the products were analyzed by X-ray diffraction, scanning electron microscopy, and mechanical property test. The results show that glass ceramics with excellent properties can be prepared by crystallization at 900℃ and annealing at 650℃ for slag melts during the cooling process. When the content of Mg2+ increased, and the precipitated crystal was a single-pyroxene-group mineral, the glass ceramics exhibited the highest mechanical properties. The content of pyroxene group mineral increased with the increasing ferronickel slag or MgO content. When the content of the two slags reached 90% (50% ferronickel slags and 40% blast furnace slags) with the addition of 2% MgO, the prepared glass ceramics presented a compact structure containing single-pyroxene-group minerals, including diopside, ordinary pyroxene, and clinopyroxene, and the best mechanical properties with flexural strength of 210 MPa and compressive strength of 1162 MPa. However, the further increase in ferronickel slag or MgO content led to the precipitation of forsterite, which significantly deteriorated the mechanical properties of glass ceramics. The increasing content of TiO2 caused no change in the type of crystals in the glass ceramics. Appropriate doping (2% in the experiments) increased the content of diopside, but excessive doping inhibited the crystal growth and reduced its performance.